(untitled) (Analele Universității București.Filosofie, 2024)
Thomas S. Kuhn’s intellectual development could be summed up in a two-stage course, first, the transition from physics to the history of science (primarily physics) and then from the history of science to the philosophy of science, a field in which he achieved consecration with The Structure of Scientific Revolutions (SSR) published in 1962. In the 1950s, before SSR, Kuhn dealt with the history of science and, finally, developed a detailed research on the case of the Copernican Revolution, publishing a book with the same name. The Copernican Revolution. Planetary Astronomy in the Development of Western Thought (CR). My aim in this paper is to argue that in this case study Kuhn identified all those situations that he will later describe in the terms of the SSR’s vocabulary, from “paradigm” and “incommensurability”, to “normal science” and “scientific revolution.” I think that although the terminological options in CR differ, such as, for example, the use of the expression “conceptual scheme” for what will later be called “paradigm”, a simple conceptual archaeology directs us to claim that CR is the immediate predecessor of SSR.